BCMA CAR-T Therapy Is Safe and Effective for Refractory/Relapsed Multiple Myeloma With Central Nervous System Involvement. Issue 1 (9th January 2022) - Wang, Yiyun; Zu, Cheng; Teng, Xinyi; Yang, Li; Zhang, Mingming; Hong, Ruimin; Zhao, Houli; Cui, Jiazhen; Xu, Huijun; Hongsheng, Alex Chang; Hu, Yongxian; Huang, He
Abstract : Central nervous system (CNS) involvement is a rare complication of multiple myeloma (MM) that portends an extremely poor prognosis. Although chimeric antigen receptor (CAR)-T cell therapy is considered a promising strategy for patients with MM, the role of CAR-T cell therapy in MM involving the CNS has not been fully elucidated. In this study, we retrospectively analyzed 4 cases of B-cell maturation antigen CAR-T cell therapy for patients with relapsed/refractory MM involving the CNS. Patients received a range of 2–7 lines of prior therapy, including 1 autologous hematopoietic stem cell transplant. The most common adverse event was cytokine release syndrome, which was observed in all 4 patients, including 2 with grade 1 and 2 with grade 2. No patient was complicated with immune effector cell–associated neurotoxicity syndrome. Within the follow-up (median: 257 d, range: 116–392 d), 3 of 4 patients reached complete remission (CR), and 1 patient reached partial response. At the data cutoff, 1 patient continued to remain in CR at day 220, and the patient with partial response died at day 116. The other 2 patients relapsed at 317 and 111 days with CR durations of 287 and 81 days, respectively. Our results show promising effectiveness and acceptable safety of CAR-T cell therapy for heavily pretreated patients with CNS MM.